Evidence of precedent wind role on controlling PM1 wet scavenging of aerosols during monsoon rain events. (15th March 2019) - Yang, L.; Pandithurai, G.; Chate, D.M.; Rao, P.S.P.; Waghmare, V.; Iyer, U.
Abstract: The role of precedent winds over fine mode (0.05–1 μm) aerosols during 2016 rainfall event is studied in this manuscript. Here, we show that concomitant wind actions influence over scavenging process during south-west monsoon rainfall over Mahabaleshwar at High Altitude Cloud Physics Laboratory (HACPL-17.56°N, 73.4°E, site altitude-1373m). During monsoon, PM1/PM10 mass ratios revealed dominance of PM1 for June, July, August, September and October as ∼80%, 90%, 98%, 97%, and 95% respectively. Fine mode aerosols and rains associated with lower precedent wind speeds ∼2 m/s were found to enhance the scavenging from ∼60 to 90% based (before minus after rainfall event) on Aerosol Chemical Speciation Monitor (ACSM) mass ( SO 4 2 −, NO 3 − ) concentrations. Similarly, before rain CCN number concentration and wind speed exhibited, −0.34 correlation coefficient (at 0.99% significance level) suggesting a viable decrease in CCN concentration due to increased wind speed. It was also observed that ventilation coefficients maxima values ∼12500 m 2 /s to be negatively correlated with before rain minima Cloud Condensation Nuclei (CCN) concentrations falling down to ∼1000 cm −3 . Moreover, three major sources such as vehicular, thunder lightning frequency and long range transport were found to control the monthly volume weighted average concentrations of rainwater. The mass ( SO 4 2 −, NO 3 − ) concentration for the monthly volume weighted averages with relatively high rainwater concentrations of NO 3 − (9.02 ± 4.71μg/m 3 ) and SO 4 2 − (11.61 ± 6.71μg/m3) for the month of June, with minimum of NO 3 − (4.11 ± 1.16 μg/m 3 ) and SO 4 2 − (9.91 ± 7.07μg/m 3 ) were seen in month of July and September respectively. However, October (16.45 ± 5.17μg/m 3, 8.08 ± 3.46μg/m 3 ) displayed an increase in both SO 4 2 − and NO 3 − rainwater concentration due to long range and increased local sources scavenging processes. Our results indicate that aerosol loading are mostly wind speed and direction driven by anthropogenic and natural origin, and have a notable impact on removal processes. Highlights: PM1 wet scavenging before minus after rainfall events by using multiple in situ instrument showed dependency over winds. High and low ventilation coefficient days showed decrease in scavenging up to ∼55% and ∼26% for SO 4 2 − and NO 3 − fine mode aerosols. High and low wind days suggest change of ∼14% and ∼37% in scavenging percentage for SO 4 2 − and NO 3 − .